Strategies for improving nurses' performance regarding cardiovascular patient's adherence to treatment regimen: Content analysis - Soroor Parvizey; Yaghoub Nadery; Parvaneh Khorasani; Aram Feizi (Wolters Kluwer Medknow Publications, 2023)
Background: Patient adherence to the treatment regimen is an important goal of treatment; finding appropriate strategies to improve treatment adherence is a nursing challenge. This study aimed to explore strategies to improve nurses' performance to enhance cardiovascular patients' adherence to treatment regimens. Materials and Methods: This is a qualitative content analysis study that was performed in an educational hospital of the Urmia University of Medical Science. Data were collected through semi-structured individual and group interviews. Sixteen individual interviews were conducted with nurses, patients, and physicians. A focus group was conducted with the presence of six nurses and nursing managers. Data were analyzed by conventional content analysis using MAXQDA 2020. Results: After analyzing the interviews, five strategies were explored; these strategies include: follow-up of the patient after discharge (systemic and organizational follow-up, educational follow-up, counseling follow-up, and motivational follow-up), sending reminders for necessary cases to the patients (risk reminders, care reminders); improving patient education methods (modern and up-to-date education, conventional and routine education), improving support services (home care services, social support, Psychological support), and optimizing the structure and processes of the hospital (making structural changes, making process changes). Conclusions: Much needs to be done to improve patient's adherence to treatment. Nurses are at the forefront of this work. In this study, we introduced ways to improve nurses' performance in order to increase patient adherence.